2017
DOI: 10.1002/rra.3196
|View full text |Cite
|
Sign up to set email alerts
|

Invasiveness screening of non‐native fishes for the middle reach of the Yarlung Zangbo River, Tibetan Plateau, China

Abstract: The aim of this study was to identify potentially invasive non-native freshwater fishes in the middle reach of the Yarlung Zangbo River, Tibetan Plateau (China), using the Aquatic Species Invasiveness Screening Kit (AS-ISK), as decision-support tool. Based on independent evaluations of 24 non-native freshwater fishes, receiver operating curve analysis identified a threshold score of ≥29 for distinguishing species likely to pose a high risk of becoming invasive from species likely to pose low-to-medium risk (<2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Therefore, special laws and regulations on introduction, aquaculture, storage and transportation of non‐native species must be developed to prevent and control invasion, and a scientific evaluation system to monitor non‐native species, such as a non‐native biological intrusion information system, is recommended. In China, the focus of control of non‐native species has so far been too concentrated on the quarantine of pests and diseases, and risk assessment has been ignored until recently (Bai, Chisholm, Sang, & Dong, ; Li, Chen, Wang, & Copp, ). The strongest factor associated with the settlement of non‐native species in the middle and downstream portions of the Pearl River was aquaculture (Gu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, special laws and regulations on introduction, aquaculture, storage and transportation of non‐native species must be developed to prevent and control invasion, and a scientific evaluation system to monitor non‐native species, such as a non‐native biological intrusion information system, is recommended. In China, the focus of control of non‐native species has so far been too concentrated on the quarantine of pests and diseases, and risk assessment has been ignored until recently (Bai, Chisholm, Sang, & Dong, ; Li, Chen, Wang, & Copp, ). The strongest factor associated with the settlement of non‐native species in the middle and downstream portions of the Pearl River was aquaculture (Gu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…FishBase; http://www.fishbase.org; cf. Bilge, Filiz, Yapici, Tarkan & Vilizzi, ; Glamuzina et al, ; Li, Chen, Wang, & Copp, ; Tarkan, Sarı, İlhan, Kurtul, & Vilizzi, ; Tarkan, Vilizzi, et al, ; Zięba, Vilizzi, & Copp, ), this study adopted an ‘integrated approach’ to determine the a priori invasiveness status of species in all other aquatic organism groups (other than freshwater and marine fishes and lampreys, as identified in AS‐ISK) due to the more limited information available.…”
Section: Methodsmentioning
confidence: 99%
“…Note that in the case of crucian carp Carassius carassius, the RA area encompasses all parts of GB because a recent genetic study has demonstrated that this species was most likely introduced about the same time as common carp Cyprinus carpio, and therefore is most likely 'not native' to southeast England as was previously believed by some scientists (Jeffries et al, 2017). A similar approach, encompassing both extant and potential future species, has been used in all published applications of AS-ISK on freshwater fishes to date (i.e., Glamuzina et al, 2017;Li et al, 2017; and in most previous applications of FISK (see Copp, 2013), as this provides a means of assessing current species, which may or may not have expressed invasive patterns. It also represents a horizon-scanning function to aid in the identification of possible future invasive species (Copp et al, 2009;Copp, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The AS-ISK is fully compliant with the 'minimum standards' (Roy et al, 2018) for assessing species under the new EU Regulation on invasive alien species of EU concern (European Union, 2014). AS-ISK has already been used successfully to screen non-native fishes in at least three risk assessment (RA) areas, including translocated species in: China (Li et al, 2017),…”
Section: Methodsmentioning
confidence: 99%